TRANSFORMASI DIGITAL PROSES PENDAFTARAN MELALUI SISTEM INFORMASI BERBASIS WEB DENGAN UI/UX MODEL - delta khairunnisa; surahmat surahmat; arif rahman; arabiatul adawiyah; rahul sabilillah; panisah panisah; zalsabila herawaty (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
Digital transformation in the world of education is one of the strategic steps to support the improvement of the quality of public services. Currently, Al-Asri Islamic Elementary School in Palembang still uses a manual method in the new student registration process, relying on paper forms, and prospective students must meet directly with the school. This manual method can cause various problems, including long queues to obtain paper forms, inefficiency in terms of time, requiring many staff to provide services, and being prone to data errors. This study aims to develop a web-based registration information system with a User Interface (UI)/User Experience (UX) approach. The method used in this study is a prototype approach, through the stages of user needs analysis, information system design, implementation, testing, and evaluation of the information system with users. The results of black box testing were 100 percent and usability testing obtained a score of 84.3 percent, with a very feasible category. This study succeeded in designing a web-based new student registration system that is able to increase the effectiveness, efficiency, and transparency of the student admission process.